Design of a position control system for a DC Motor using a DSP56002EVM - Inca, Jorge Luis (2018)
In this work the methods of adaptive control and self-tuning control are exposed using a card of microcontroller DSP56002evm. The system of DC motor with rotor joined mechanically to an aluminum rod, uses digital controller which is carried out by means of a digital signal processor (DSP) that is programmed in its own assembler language.